(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2011)
This assignment deals with Dr. A.P.J Abdul Kalam’s concept of education and its relevance. Education is bound up with human race. Its boundaries are as wide as those at life. Its implications are rich and varied. Just as it is difficult to squeeze life in a few words, is the same way it is difficult to give a single meaning or definition of education. The writers and philosophers are the actual teachers who often express their ideas for the benefits of the society. Education cannot be separated from life and people having different outlooks understand the life from different angles of vision. Dr. A.P.J Abdul Kalam is to be looked at within his cultural background this total rural citizen from the far end of India, Rameshwaram, coming from a boatman’s family goes up to heights because of his sheer brilliance combined with simplicity of the highest and a rare sense of uncommon humility. In fact he is a remarkable thinker of the highest order.